PRE-ERUPTIVE CRYSTALLIZATION CONDITIONS OF MAFIC AND SILICIC MAGMAS AT THE PLAT PAYS VOLCANIC COMPLEX, DOMINICA (LESSER ANTILLES) - Halama R.; Boudon G.; Villemant B.; Le Friant A.; Komorowski J.-C.; Joron J.-L. (My University, 2006)
Andesitic to dacitic magmas of the Plat Pays volcanic complex (Dominica, Lesser Antilles) that erupted during the last ~100 ka equilibrated at temperatures of 800-880 °C and total pressures of 1.1-2.3 kbar. Magmatic conditions were moderately oxidizing (fO2 ~1.5 ± 0.3 log units above FMQ) and estimated melt water contents vary from 5.2 to 6.5 wt.%. The crystal-rich nature of the samples, the relatively narrow bulk rock compositional range and the similarity of the intensive crystallization parameters throughout the sample suite are consistent with the presence of a long-lived, highly crystallized magma reservoir. Further crystallization during ascent produced highly evolved rhyolitic glass compositions. The silicic magma reservoir was occasionally invaded by more mafic melts of basaltic andesitic to basaltic composition. These were rarely erupted, but they mixed with the silicic magmas and were frequently incorporated as mafic enclaves. The mafic magmas record temperatures of ~1060 °C at fO2 = 1.6-2.0 log units above FMQ. The similarities in mineralogy, petrology and inferred magma storage conditions of the Plat Pays volcanic complex with the Soufriere Hills volcano, Montserrat, and Montagne Pelée, Martinique, can serve as a useful guide for forecasting and evaluation of possible future eruptions. © 2006 Elsevier B.V. All rights reserved.
Keywords: DOMINICA; GEOTHERMOBAROMETRY; LESSER ANTILLES; PETROLOGY; PLAT PAYS VOLCANIC COMPLEX; QUILF